2017
DOI: 10.1021/acsomega.7b00365
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Water Layers on Graphene Surfaces

Abstract: Although graphitic materials were thought to be hydrophobic, recent experimental results based on contact angle measurements show that the hydrophobicity of graphitic surfaces stems from airborne contamination of hydrocarbons. This leads us to question whether a pristine graphitic surface is indeed hydrophobic. To investigate the water wettability of graphitic surfaces, we use molecular dynamics simulations of water molecules on the surface of a single graphene layer at room temperature. The results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 57 publications
(92 reference statements)
12
71
0
Order By: Relevance
“…In addition, the structure of graphene itself can also play an important role in response to the temperaturedependent ion adsorption. A simulation study has reported that water could form an ice-like double layer structure on free standing graphene, preventing the interaction between graphene and the bulk solution [24]. This interfacial water structure was found disrupted at 340 K (67 °C), which is close to where we observed enhanced ion adsorption.…”
Section: A N U S C R I P Tsupporting
confidence: 69%
See 3 more Smart Citations
“…In addition, the structure of graphene itself can also play an important role in response to the temperaturedependent ion adsorption. A simulation study has reported that water could form an ice-like double layer structure on free standing graphene, preventing the interaction between graphene and the bulk solution [24]. This interfacial water structure was found disrupted at 340 K (67 °C), which is close to where we observed enhanced ion adsorption.…”
Section: A N U S C R I P Tsupporting
confidence: 69%
“…The ion adsorption was enhanced by heating the solution to 60 ºC, which was retained after cooling. We attributed this change to the higher ion mobility, the higher ion affinity of the formed silanol layer on the substrate, and the disruption of the ordered water structure at high temperatures as reported previously [24].…”
Section: Summary and Concluding Remarkssupporting
confidence: 66%
See 2 more Smart Citations
“…3d. Then, O2 molecules adsorb onto the H2O layer as an over-layer; a study based on molecular dynamics simulation 19 has shown that H2O molecules form a double-layer structure on graphene, but here the second H2O monolayer is omitted for simplicity. When the gate voltage is applied to a graphene FET, electric field lines are formed, as schematically depicted in Fig.…”
Section: Peculiar Dependence On Gate-voltage Polaritymentioning
confidence: 99%